Drought spells over north-central India during the 1979 southwest monsoon - MOHAN, H. S. RAM; VAISALA, P.; RAO, B. V. APPA (MAUSAM, 1983)
Widespread drought spells were observed over north-central India during the 1979 summer monsoon. An attempt has been made in the present paper to study the impact of drought conditions on the short period water balances of representative stations in the region, following the bookkeeping procedure of Thornthwaite and Mather ( 1955) .Cumulative deviation techniques have been used to delineate and categorise the intensity and duration of drought spells.